Effect of a stable prostacyclin analogue on canine renal allograft rejection. - Tobimatsu, M (1987)
The effect of OP-41483 (Ono Pharmaceutical Co., Osaka, Japan), a stable prostacyclin analogue, on canine renal allograft rejection was investigated. Administration for 4 days after transplantation significantly increased renal cortical blood flow and urine output when compared with untreated dogs with renal allografts. Serum creatinine levels remained relatively low during postoperative days 1-4. Mean animal survival time was prolonged. Vascular lesions and mononuclear cell infiltration were greatly diminished in biopsy specimens removed on day 4. This stable prostacyclin analogue provided a degree of protection against canine renal allograft rejection.